Identificación de haplogrupos mitocondriales en pacientes con Neuromielitis Óptica, un estudio de casos y controles (2023)
Neuromyelitis Optica (NMO) is an autoimmune, inflammatory, and demyelinating disorder of the central nervous system, mainly affecting the optic nerve and spinal cord. The aim of this study is to identify mitochondrial haplogroups in patients with NMO from Bogotá and Medellín, Colombia. For this purpose, a case-control analysis was performed, genomic DNA was isolated and purified from venous blood samples. Through PCR, the hypervariable region 1 of mitochondrial DNA was amplified and haplogroups were determined using HaploGrep software. Afterwards, a statistical analysis was performed to evaluate the meaning of the results. For instance, Native American haplogroups (A, B, C and D) showed a higher prevalence in the whole population, the cities of Bogota and Medellin were mostly influenced by European and African haplogroups, respectively. Finally, no significant differences were observed in the distribution of haplogroups between patients and controls, in the general population and for each study city. However, differences were found for haplogroups between the population of Bogota and Medellín. Mitochondrial haplogroups in the population are not directly associated with the disease.